Growth patterns of preterm and small for gestational age children during the first 10 years of life - Nguyen, Phuong Thi; Nguyen, Phuong Hong; Tran, Lan Mai; Khuong, Long Quynh; Nguyen, Son Van; Young, Melissa F.; Ramakrishnan, Usha (Frontiers in Nutrition, 2024)
Background: Preterm and small for gestational age (SGA) remain significant public health concerns worldwide. Yet limited evidence exists on their growth patterns during childhood from low-or middle-income countries.We investigated the postnatal growth patterns of preterm and SGA compared to term appropriate for gestational age (AGA) children from birth to 10 -11y, and examined the impact of birth status on child nutritional status during the school age years.Children born to women who participated in a double-blinded randomized controlled trial of preconception micronutrient supplementation in Vietnam were classified into 3 groups: preterm AGA (n = 130), full-term SGA (n = 165) and full-term AGA (n= 1072). Anthropometric data (weight and height) were collected prospectively at birth, 3, 6, 12, 18, 24 months and at 6-7 and 10-11y. We used ANOVA and multiple regression models to examine the differences in growth patterns from birth to 10-11y as well as child undernutrition and overnutrition by birth status.Results: Children who were born preterm exhibited rapid postnatal growth, but still had lower HAZ at 1y and 2y and showed catch up to the AGA group at 6y. Compared to those born AGA, SGA infants had higher risk of thinness (BMIZ < -2) at 2y and 6y (adjusted Odds Ratio, AOR [95% CI] 2.5 [1.0, 6.1]) and 2.6 [1.4,4.6], respectively); this risk reduced at 10-11y (1.6 [0.9, 2.8]). The risk of stunting (HAZ < -2) was also 2.4 [1.5,3.8] and 2.3 times [1.2,4.1] higher in SGA than AGA group at ages 2y and 6-7y, respectively, with no differences at 10y. Although preterm children had higher rates of thinness and stunting at 2y compared to AGA children, these differences were not statistically significant. No associations were found between preterm or SGA and overweight /obesity at age 10-11y.Children who were born term-SGA continued to demonstrate deficits in weight and height during childhood whereas those born preterm showed catch-up growth by age 6-7y.Additional efforts to reduce the burden of these conditions are needed, particularly during school-age and early adolescents when children are exposed to challenging environments and have higher demands for nutrition.